Film for inner container of bag-in-box, inner container of bag-in-box, bag-in-box and method for selecting film for inner container of bag-in-box
Patent Information
- Application Number
- JP2023125686
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
AI Technical Summary
【0009】 本開示によれば、リサイクル適性及び落袋耐性に優れシワの発生が抑制されたバッグインボックス用内容器及び当該内容器を備えるバッグインボックスが提供される。また、本開示によれば、このようなバッグインボックス用内容器の製造に有用なバッグインボックスの内容器用のフィルム及びフィルムの選定方法が提供される
Smart Images

Figure 2025021750000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a film for a bag-in-box inner container, an inner container for a bag-in-box, a bag-in-box, and a method for selecting a film for a bag-in-box inner container. [Background technology]
[0002] In recent years, with the growing environmental awareness regarding global warming, marine plastic waste, etc., there is a demand for further efficiency in the sorting and recovery of plastic materials and recycling. Even for conventional packaging laminates that have been improved in performance by combining different materials, there is a demand for mono-material laminates in order to improve recyclability. For example, Patent Document 1 discloses a mono-material gas barrier laminate that is mainly composed of a polyolefin film and has excellent recyclability. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2021 / 176948 Summary of the Invention [Problem to be solved by the invention]
[0004] Incidentally, one of the applications of plastic materials is an inner container in a bag-in-box. The bag-in-box includes a flexible inner container made of a plastic film and an outer container (outer container) that houses the inner container. The outer container is, for example, a box made of cardboard. In the process of manufacturing this bag-in-box, after filling the plastic inner container with liquid, it may be subjected to an impact from being dropped when storing it in the outer container, causing the inner container to break and resulting in leakage of the contents.
[0005] The inventors selected polyethylene resin as a material for realizing mono-materialization. The inventors' investigation revealed that the above-mentioned problem of bag breakage becomes significant when the inner container is made of polyethylene resin.
[0006] Furthermore, the inventors' investigations revealed that in an inner container film containing a polyethylene resin, wrinkles occur due to heat damage during bag production.
[0007] The present disclosure provides a bag-in-box inner container having excellent recyclability and drop-bag resistance and suppressed wrinkle generation, and a bag-in-box including the inner container. The present disclosure also provides a film for the bag-in-box inner container and a method for selecting the film, which are useful for manufacturing such a bag-in-box inner container. [Means for solving the problem]
[0008] In order to solve the above problems, the present disclosure provides the following film for a bag-in-box inner container, an inner container for a bag-in-box, a bag-in-box, and a method for selecting a film for a bag-in-box inner container. [1] A film for a bag-in-box inner container, A first polyethylene resin layer; An adhesive layer; A second polyethylene resin layer; in this order, Satisfying the following formula (1), The thickness of the film is 200 μm or less. 2.0≦W2 / W1...Equation (1) [In formula (1), W1 is the mass of a dart at which the first polyethylene-based resin layer is destroyed as measured in accordance with JIS K 7124-1 A method, and W2 is the mass of a dart at which the second polyethylene-based resin layer is destroyed as measured in accordance with JIS K 7124-1 A method.] [2] The film according to [1], wherein the adhesive layer has gas barrier properties. [3] The film according to [1] or [2], wherein the adhesive layer has a thickness of 0.5 to 6.0 μm. [4] The film according to any one of [1] to [3], wherein the first polyethylene-based resin layer and the second polyethylene-based resin layer are unstretched films. [5] The film according to any one of [1] to [4], wherein at least one of the first polyethylene-based resin layer and the second polyethylene-based resin layer has a stiffness strength in MD and TD of 30 to 300 mN. [6] An inner container for a bag-in-box, produced by forming a bag from the film according to any one of [1] to [5]. [7] A bag-in-box comprising an inner container having a spout and an outer container for housing the inner container, the inner container being the inner container for bag-in-box described in [7]. [8] A method for selecting a film for a bag-in-box container, comprising the steps of: A step of preparing a film to be evaluated, the film having a first polyethylene-based resin layer, an adhesive layer, and a second polyethylene-based resin layer in this order and a thickness of 200 μm or less; preparing a first test piece comprising a first polyethylene-based resin layer and a second test piece comprising a second polyethylene-based resin layer; A step of determining the mass (W1) of the dart at which the first test piece is broken, which is measured in accordance with JIS K 7124-1 A method; A step of determining the mass (W2) of the dart at which the second test piece is broken, which is measured in accordance with JIS K 7124-1 A method; determining that the film is acceptable when the mass ratio (W2 / W1) of the mass (W1) of the dart that breaks the first test piece to the mass (W2) of the dart that breaks the second test piece is 2.0 or more; The film selection method includes: Effect of the Invention
[0009] According to the present disclosure, there are provided a bag-in-box inner container having excellent recyclability and drop-bag resistance and suppressed wrinkle generation, and a bag-in-box including the inner container. In addition, according to the present disclosure, there are provided a film for the bag-in-box inner container and a method for selecting the film, which are useful for manufacturing such a bag-in-box inner container. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a cross-sectional view showing one embodiment of a film for an inner container of a bag-in-box. [Diagram 2] FIG. 2 is an external view showing one embodiment of the bag-in-box inner container. [Diagram 3] FIG. 3 is an external view showing one embodiment of the bag-in-box. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, embodiments of the present disclosure will be described in detail. However, the present disclosure is not limited to the following embodiments.
[0012] <Film for bag-in-box containers> Fig. 1 is a cross-sectional view showing one embodiment of a film for an inner container of a bag-in-box. The film for an inner container of a bag-in-box (hereinafter sometimes referred to as "film for an inner container") 10 comprises a first polyethylene-based resin layer (hereinafter sometimes referred to as "first layer") 1, an adhesive layer 3, and a second polyethylene-based resin layer (hereinafter sometimes referred to as "second layer") 2, in this order. The film for an inner container 10 satisfies the following formula (1). The thickness of the film for an inner container 10 is 200 µm or less.
[0013] 2.0≦W2 / W1...Equation (1) [In formula (1), W1 is the mass of a dart at which the first polyethylene-based resin layer is destroyed as measured in accordance with JIS K 7124-1 A method, and W2 is the mass of a dart at which the second polyethylene-based resin layer is destroyed as measured in accordance with JIS K 7124-1 A method.]
[0014] The film 10 for inner container is useful for manufacturing inner containers for bag-in-boxes that have excellent resistance to dropping and suppress the occurrence of wrinkles. The inventors speculate as follows about the reason why such an effect is achieved. That is, when the bag is dropped, an anisotropic impact is applied to the film by the contents contained in the inner container. This impact causes local distortion in the film, causing the bag to break. It is possible to make the film thicker in order to suppress the bag from breaking. However, in the bag making process, two opposing films are thermally bonded using impulse sealing and heat sealing. At this time, heat is applied from the outermost layer of the film and transferred to the innermost layer, thereby melting the innermost layer. Therefore, if the film is thick, the amount of heat supplied increases. As a result, the outermost layer is thermally damaged, causing defects such as wrinkles. However, in the film 10, the ratio (W2 / W1) of the mass (W1) of the dart that breaks the first layer to the mass (W2) of the dart that breaks the second layer is 2.0 or more. This suppresses the occurrence of the above-mentioned local distortion in the film 10, even though the film 10 has a thickness of 200 μm or less. As a result, the film 10 is useful for manufacturing a bag-in-box inner container that has excellent drop-bag resistance and suppresses the occurrence of wrinkles.
[0015] The inner container film can be used to make an inner container bag with either the first layer 1 or the second layer 2 on the inside. The first layer 1 and the second layer 2 can be called base films.
[0016] The film for the inner container may have gas barrier properties from the viewpoint of storage stability of the contents. Specifically, the oxygen permeability of the film for the inner container at 30°C / 70 RH% is 200 cc / m 2 ·day·atm or less is preferable, and 100cc / m 2It is more preferable that the oxygen permeability is 100 MPa or less.
[0017] The film for an inner container preferably contains polyethylene at a ratio of 90% by mass or more. Here, the ratio of polyethylene in the film for an inner container means the ratio of the total amount of polyethylene to the total amount of resin material in each layer constituting the film for an inner container. By making the ratio of polyethylene 90% by mass or more, high recyclability can be achieved.
[0018] The thickness of the inner container film is 200 μm or less, preferably 180 μm or less, more preferably 160 μm or less, in order to prevent the weight of the inner container from becoming too heavy and to reduce the amount of resin material contained in the inner container. The thickness of the inner container film is preferably 80 μm or more, more preferably 110 μm or more, in order to further prevent the bag from breaking when dropped.
[0019] (First layer and second layer) The first layer and the second layer contain polyethylene. The first layer and the second layer are preferably made of only polyethylene. The polyethylene contained in the first layer and the second layer may be a homopolymer of ethylene or a copolymer of ethylene and another monomer. When the polyethylene is a copolymer of ethylene and another monomer, the ratio of units derived from ethylene in the copolymer is, for example, 80 mol % or more.
[0020] The other monomers are, for example, α-olefins. According to one example, the α-olefins have a carbon number in the range of 3 to 20. Such α-olefins include, for example, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene. The polyethylene may be a copolymer of ethylene and one of vinyl acetate and acrylic esters.
[0021] Examples of the polyethylene contained in the first layer and the second layer include high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE) and very low density polyethylene (VLDPE). From the viewpoint of sealability and pinhole resistance at low temperatures, the polyethylene is preferably linear low density polyethylene. Linear low density polyethylene is more flexible than other polyethylenes, and therefore has excellent flexibility as a film (it has excellent bending resistance, which contributes to improving pinhole resistance). In other words, it is preferable that the first layer and the second layer contain linear low density polyethylene as a main component. The term "main component" as used herein means a component contained in an amount of 50 to 100 mass%, preferably 70 to 100 mass%, and more preferably 90 to 100 mass% based on the total amount of the layer.
[0022] Here, high density polyethylene has a density of 0.942 g / cm 3 and medium density polyethylene has a density of 0.930 g / cm 3 More than 0.942g / cm 3 and low density polyethylene has a density of 0.910 g / cm 3 More than 0.930g / cm 3 Linear low density polyethylene has a density of 0.910 g / cm 3 More than 0.930cm 3 and ultra-low density polyethylene has a density of 0.910 g / cm 3The density is a value obtained by a method in accordance with JIS K7112:1999.
[0023] The first layer and the second layer may contain additives such as antistatic agents, ultraviolet absorbers, plasticizers, etc. as minor components. The first layer and the second layer may contain 90% by mass or more, preferably 95% by mass or more, of polyethylene, that is, the layers may be layers substantially made of polyethylene. The first layer and the second layer may be layers made of polyethylene. The polyethylenes contained in the first layer and the second layer may be the same or different.
[0024] Each of the first layer and the second layer may be a single layer independently, or may be a laminate in which layers containing polyethylene are laminated together. When the layer is a laminate, the constituent materials of the individual layers may be the same or different.
[0025] The first layer and the second layer may be subjected to a surface treatment such as a plasma treatment in order to improve adhesion to the adjacent layer.
[0026] The first layer and the second layer may be a stretched film or an unstretched film, but an unstretched film is preferable because it has better uniform drop resistance even if the inner container is subjected to impacts from various directions. From the viewpoints of gas barrier properties and heat resistance, a stretched film is preferable. Examples of the stretched film include uniaxially stretched films and biaxially stretched films, but from the viewpoints of heat resistance and cold resistance, a biaxially stretched film is preferable.
[0027] The thickness of each of the first layer and the second layer can be 30 to 120 μm. When the thickness is 30 μm or more, the strength of the layer can be easily improved. When the thickness is 120 μm or less, the flexibility of the layer is further improved, and pinhole resistance can be more easily obtained. From these viewpoints, the thickness of each of the first layer and the second layer is more preferably 40 to 100 μm, and further preferably 50 to 80 μm.
[0028] The thickness of the first layer and the second layer may be the same or different. The ratio of the thickness of the first layer to the thickness of the second layer may be, for example, 1:1 to 1:3, or may be 1:1 to 1:2. When the thickness ratio is within the above range, there is a tendency for pinhole resistance to be excellent while maintaining economic efficiency and environmental compatibility.
[0029] The W2 / W1 on the right side of the above formula (1) is 2.0 or more, and since this tends to result in better resistance to dropped bags, it is preferably 2.5 or more, and more preferably 2.7 or more. W2 / W1 may be, for example, 8.0 or less. W2 / W1 can be changed by adjusting the thickness ratio of the first layer and the second layer and the tensile modulus of elasticity described later.
[0030] The stiffness strength of the first layer in MD is preferably 30 to 300 mN because the resistance to dropping a bag tends to be even better.The stiffness strength of the first layer in TD is preferably 30 to 300 mN because the resistance to dropping a bag tends to be even better.
[0031] The stiffness strength of the second layer in MD is preferably 30 to 300 mN because the second layer tends to have better resistance to dropping a bag.The stiffness strength of the second layer in TD is preferably 30 to 300 mN because the second layer tends to have better resistance to dropping a bag.
[0032] In this specification, "stiffness" refers to the strength obtained by the loop stiffness method. More specifically, "stiffness" refers to the stiffness of a sample measured by the load applied when the sample is cut into a loop of a specified width and length and crushed. For example, it can be measured using a commercially available measuring device called a loop stiffness tester. In this specification, stiffness is measured using a sample with a width of 15 mm and a length of 100 mm under the conditions of a loop length of 50 mm and an indentation length of 10 mm.
[0033] In this specification, "MD" means "Machine Direction" and refers to the flow direction in the production of the film, and "TD" means "Transverse Direction" and refers to the direction perpendicular to MD in the plane of the film.
[0034] The tensile modulus of the first layer and the second layer at 23°C may be 400MPa or less in both MD and TD. Since pinholes occurring during transportation of the bag-in-box occur due to bending that does not depend on the direction of the film, the tensile modulus of the MD and TD may be within the above range. By having a tensile modulus of 400MPa or less, it is possible to suppress the occurrence of pinholes during bending, compared with a case where the tensile modulus is more than 400MPa. In addition, by having a tensile modulus of 400MPa or less, it is easy to obtain an inner container film with excellent processability. From this viewpoint, the tensile modulus of the MD and TD is more preferably 250MPa or less.
[0035] The lower limit of the tensile modulus is not particularly limited, but is preferably 100 MPa or more, more preferably 150 MPa or more, in both MD and TD. At least one of the first layer and the second layer may satisfy these lower limits of the modulus. When the numerical range is as above, the occurrence of processing defects such as elongation and flapping during film processing and inner container bag making tends to be suppressed. In addition, the adhesion between the films is suppressed, which improves the dischargeability of the contents and tends to make the contents less likely to remain.
[0036] The tensile modulus (MPa) can be measured as follows. The films to be used as the first layer and the second layer are cut into strips with a total length of 200 mm and a width of 15 mm to prepare test pieces, which are attached to the fixed and movable grips of a tensile testing machine (a testing device conforming to JIS K7127:1999) with a distance between the grips of 150 mm. The test temperature is set to 23°C, the movable gripper is moved at a tensile speed of 50 mm / min, and the ratio of the tensile stress to the corresponding strain within the tensile proportional limit is determined. The average value for three test pieces is taken as the tensile modulus. The measurement result of a test piece cut in the machine direction of the film as the overall length direction of the strip is taken as the MD tensile modulus, and the measurement result of a test piece cut in the width direction of the film as the overall length direction of the strip is taken as the TD tensile modulus.
[0037] (adhesive layer) The adhesive layer is not particularly limited as long as it contains a component capable of bonding the first layer and the second layer. The adhesive layer may or may not have gas barrier properties (oxygen permeation suppression properties). Examples of gas barrier adhesives for forming an adhesive layer having gas barrier properties include epoxy adhesives, polyester-polyurethane adhesives, and the like. The adhesive is cured to form a gas barrier adhesive layer, and the gas barrier properties are expressed. Examples of gas barrier adhesives include Maxive manufactured by Mitsubishi Gas Chemical Company, Inc., and PASLIM manufactured by DIC Corporation.
[0038] By using a gas barrier adhesive, it is possible to achieve excellent gas barrier properties while suppressing the thickness of the adhesive layer (while maintaining recyclability). The thickness of the adhesive layer can be 0.5 to 6.0 μm. When the thickness is 0.5 μm or more, it is easy to obtain sufficient gas barrier properties and sufficient adhesive strength. When the thickness is 6.0 μm or less, there is a tendency that the solvent is less likely to remain in the adhesive layer. From these viewpoints, the thickness of the gas barrier adhesive layer is more preferably 0.8 to 5.0 μm, and even more preferably 1.0 to 4.5 μm.
[0039] Specific examples of gas barrier adhesives include epoxy resin compositions containing an epoxy resin, an epoxy resin curing agent including an amine-based curing agent, and an unsaturated fatty acid amide having a carbon number of 14 to 24. Examples of such gas barrier adhesives include Maxive manufactured by Mitsubishi Gas Chemical Company, Inc.
[0040] The epoxy resin may be any of a saturated or unsaturated aliphatic compound, alicyclic compound, aromatic compound, or heterocyclic compound. In consideration of the development of high gas barrier properties, however, an epoxy resin containing an aromatic ring or alicyclic structure in the molecule is preferred.
[0041] The epoxy resin may be at least one resin selected from the group consisting of epoxy resins having a glycidylamino group derived from meta-xylylenediamine, epoxy resins having a glycidylamino group derived from para-xylylenediamine, epoxy resins having a glycidylamino group derived from 1,3-bis(aminomethyl)cyclohexane, epoxy resins having a glycidylamino group derived from 1,4-bis(aminomethyl)cyclohexane, epoxy resins having a glycidylamino group derived from diaminodiphenylmethane, epoxy resins having a glycidylamino group and / or a glycidyloxy group derived from para-aminophenol, epoxy resins having a glycidyloxy group derived from bisphenol A, epoxy resins having a glycidyloxy group derived from bisphenol F, epoxy resins having a glycidyloxy group derived from phenol novolac, and epoxy resins having a glycidyloxy group derived from resorcinol. These epoxy resins may be used alone, or may be used in combination of two or more from the viewpoint of improving flexibility, impact resistance, moist heat resistance, etc.
[0042] Among the above, from the viewpoint of gas barrier properties, the epoxy resin is preferably one whose main component is at least one selected from the group consisting of epoxy resins having a glycidylamino group derived from metaxylylenediamine, epoxy resins having a glycidylamino group derived from paraxylylenediamine, and epoxy resins having a glycidyloxy group derived from bisphenol F, and more preferably one whose main component is an epoxy resin having a glycidylamino group derived from metaxylylenediamine. The meaning of the main component is as described above.
[0043] The epoxy resin curing agent contains an amine-based curing agent from the viewpoint of exhibiting high gas barrier properties. As the amine-based curing agent, polyamines or modified products thereof that have been conventionally used as epoxy resin curing agents can be used. From the viewpoint of obtaining high gas barrier properties, the amine-based curing agent is preferably a modified product of polyamine. The epoxy resin curing agent may contain a curing agent component other than the amine-based curing agent, but from the viewpoint of obtaining high gas barrier properties, it is preferable that the content of the amine-based curing agent is high. From the viewpoint of obtaining high gas barrier properties, the content of the amine-based curing agent in the epoxy resin curing agent is preferably 50% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more. The upper limit is 100% by mass.
[0044] The mixing ratio of the epoxy resin and the epoxy resin curing agent in the epoxy resin composition is not particularly limited. For example, the ratio of the number of active amine hydrogens in the epoxy resin curing agent to the number of epoxy groups in the epoxy resin (the number of active amine hydrogens in the epoxy resin curing agent / the number of epoxy groups in the epoxy resin) may be in the range of 0.2 to 12.0, 0.4 to 10.0, 0.6 to 8.0, more than 1.0 and 5.0 or less, or 1.1 to 3.5.
[0045] An adhesive layer with good transparency can be formed by using an unsaturated fatty acid amide having 14 to 24 carbon atoms. The unsaturated fatty acid amide has 14 to 24 carbon atoms, preferably 16 to 24, and more preferably 18 to 22, from the viewpoints of less blocking, better conformability to the base layer, and better transparency.
[0046] The unsaturated fatty acid constituting the unsaturated fatty acid amide may be a fatty acid having at least one unsaturated bond and a carbon number of 14 to 24. The number of unsaturated bonds in the unsaturated fatty acid is preferably 1 to 6, more preferably 1 to 4, and even more preferably 1 to 2.
[0047] Examples of unsaturated fatty acids constituting the unsaturated fatty acid amide include monounsaturated fatty acids such as myristoleic acid, sapienic acid, palmitoleic acid, oleic acid, elaidic acid, vaccenic acid, gadoleic acid, eicosenoic acid, erucic acid, and nervonic acid; diunsaturated fatty acids such as linoleic acid, eicosadienoic acid, and docosadienoic acid; triunsaturated fatty acids such as linolenic acid, pinolenic acid, eleostearic acid, mead acid, and eicosatrienoic acid; tetra-fatty acids such as stearidonic acid, arachidonic acid, eicosatetraenoic acid, and adrenic acid; and one or more of these can be used in combination. Among these, from the viewpoint of transparency, at least one selected from the group consisting of monounsaturated fatty acids and diunsaturated fatty acids having 14 to 24 carbon atoms is preferred, monounsaturated fatty acids having 14 to 24 carbon atoms are more preferred, monounsaturated fatty acids having 16 to 24 carbon atoms are more preferred, and monounsaturated fatty acids having 18 to 22 carbon atoms are more preferred.
[0048] From the viewpoints of reducing blocking and improving conformability to the base layer and transparency, the unsaturated fatty acid amide is preferably at least one selected from the group consisting of palmitoleic acid amide, oleic acid amide, eicosenoic acid amide, and erucic acid amide, and more preferably at least one selected from the group consisting of oleic acid amide and erucic acid amide.
[0049] The content of the unsaturated fatty acid amide in the epoxy resin composition is 0.1 to 20 parts by mass, 0.2 to 15 parts by mass, 0.5 to 15 parts by mass, 1 to 15 parts by mass, 3 to 15 parts by mass, or 5 to 12 parts by mass, based on 100 parts by mass of the total amount of the epoxy resin and the non-volatile content in the epoxy resin curing agent. If the content of the unsaturated fatty acid amide is 0.1 parts by mass or more based on 100 parts by mass of the total amount of the epoxy resin in the epoxy resin composition and the non-volatile content in the epoxy resin curing agent, it is easy to obtain the conformability to the base layer and the blocking suppression effect. Also, if it is 20 parts by mass or less, it is easy to maintain high gas barrier properties and transparency, and it is easy to suppress the elution of the unsaturated fatty acid amide.
[0050] The epoxy resin composition may further contain non-spherical inorganic particles. By containing non-spherical inorganic particles in the epoxy resin composition, the gas barrier property and flex resistance can be further improved.
[0051] The shape of the non-spherical inorganic particles may be any three-dimensional shape other than a sphere (almost perfect sphere), such as a plate-like, scaly, columnar, chain-like, fibrous, etc. Plate-like and scaly inorganic particles may be laminated to form a layer. Among these, from the viewpoint of improving gas barrier properties and bending resistance, plate-like, scaly, columnar, or chain-like inorganic particles are preferred, plate-like, scaly, or columnar inorganic particles are more preferred, and plate-like or scaly inorganic particles are even more preferred.
[0052] Examples of inorganic substances constituting the non-spherical inorganic particles include silica, alumina, mica, talc, aluminum, bentonite, smectite, etc. Among these, from the viewpoint of improving gas barrier properties and flex resistance, at least one selected from the group consisting of silica, alumina, and mica is preferred, at least one selected from the group consisting of silica and alumina is more preferred, and silica is even more preferred.
[0053] The average particle size of the non-spherical inorganic particles is preferably in the range of 1 to 2000 nm, 1 to 1500 nm, 1 to 1000 nm, 1 to 800 nm, 1 to 500 nm, 5 to 300 nm, 5 to 200 nm, 5 to 100 nm, or 8 to 70 nm. If the average particle size is 1 nm or more, the inorganic particles are easy to prepare, and if it is 2000 nm or less, the gas barrier properties, bending resistance, and transparency are all good. Note that the average particle size is the average particle size of primary particles.
[0054] When non-spherical inorganic particles are used, the content of the non-spherical inorganic particles in the epoxy resin composition is preferably 0.5 to 10.0 parts by mass, 1.0 to 8.0 parts by mass, 1.5 to 7.5 parts by mass, or 3.0 to 7.0 parts by mass, based on 100 parts by mass of the total amount of the epoxy resin and the epoxy resin curing agent. If the content of the non-spherical inorganic particles in the epoxy resin composition is 0.5 parts by mass or more based on 100 parts by mass of the total amount of the epoxy resin and the epoxy resin curing agent, the effect of improving the gas barrier property and the flex resistance is good. In addition, if the content is 10.0 parts by mass or less, the transparency is also good.
[0055] The epoxy resin composition may contain additives such as a thermosetting resin, a wetting agent, a tackifier, an antifoaming agent, a curing accelerator, an anti-rust additive, a pigment, and an oxygen scavenger, if necessary. The total content of the epoxy resin, the epoxy resin curing agent, and the unsaturated fatty acid amide having 14 to 24 carbon atoms in the solid content of the epoxy resin composition is preferably 60 mass% or more, 70 mass% or more, 80 mass% or more, or 85 mass% or more, and the upper limit is 100 mass%. The "solid content of the epoxy resin composition" means the components in the epoxy resin composition excluding water and organic solvents.
[0056] A specific example of the gas barrier adhesive is a resin composition for adhesives that contains a polyol having two or more hydroxyl groups in one molecule, an isocyanate compound having two or more isocyanate groups in one molecule, and a phosphoric acid-modified compound, and the polyol has one or more main skeletons selected from the group consisting of a polyester structure, a polyester polyurethane structure, a polyether structure, and a polyether polyurethane structure. The resin composition for adhesives may further contain a plate-like inorganic compound.
[0057] A specific example of such an adhesive resin composition containing a polyol, an isocyanate compound, and a phosphoric acid-modified compound is PASLIM manufactured by DIC Corporation.
[0058] The glass transition temperature of the cured coating film of the adhesive resin composition is preferably in the range of -30°C to 80°C. More preferably, it is 0°C to 70°C. Still more preferably, it is 25°C to 70°C. If the glass transition temperature is higher than 80°C, the flexibility of the cured coating film at around room temperature decreases, and the adhesion to the substrate film may be inferior, resulting in a decrease in adhesive strength. On the other hand, if the glass transition temperature is lower than -30°C, the molecular motion of the cured coating film at around room temperature may be so intense that sufficient gas barrier properties may not be obtained, or the adhesive strength may decrease due to insufficient cohesive strength.
[0059] The polyester structure in the polyol is obtained by polycondensation reaction of polycarboxylic acids and polyhydric alcohols by a known and conventional method. Examples of the polycarboxylic acids include aliphatic polycarboxylic acids and aromatic polycarboxylic acids. Specific examples of the aliphatic polycarboxylic acids include succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid.
[0060] Specific examples of aromatic polyvalent carboxylic acids include polybasic acids such as orthophthalic acid, terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,2-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, and anhydrides or ester-forming derivatives of these dicarboxylic acids; p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, and ester-forming derivatives of these dihydroxycarboxylic acids.
[0061] Specific examples of ortho-oriented aromatic dicarboxylic acids include orthophthalic acid, 1,2-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, and anhydrides or ester-forming derivatives of these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more. The polyhydric alcohols may include aliphatic polyhydric alcohols and aromatic polyhydric phenols.
[0062] Specific examples of aliphatic polyhydric alcohols include ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, cyclohexanedimethanol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, dimethylbutanediol, butylethylpropanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, and tripropylene glycol.
[0063] Specific examples of aromatic polyhydric phenols include hydroquinone, resorcinol, catechol, naphthalenediol, biphenol, bisphenol A, bisphenol F, tetramethylbiphenol, and ethylene oxide-extended products and hydrogenated alicyclic derivatives thereof.
[0064] The isocyanate compound has two or more isocyanate groups in the molecule, and may be either aromatic or aliphatic, and may be either a low molecular weight compound or a high molecular weight compound, and known compounds such as diisocyanate compounds having two isocyanate groups or polyisocyanate compounds having three or more isocyanate groups can be used. The isocyanate compound may be a blocked isocyanate compound obtained by addition reaction using a known isocyanate blocking agent by a known and commonly used appropriate method.
[0065] Among these, polyisocyanate compounds are preferred from the standpoint of adhesion and retort resistance, and from the standpoint of imparting gas barrier properties, those having an aromatic ring are preferred, and in particular, isocyanate compounds containing a meta-xylene skeleton are preferred because they can improve gas barrier properties not only through hydrogen bonding of the urethane groups but also through π-π stacking between aromatic rings.
[0066] Specific examples of the isocyanate compound include adducts, biurets, and allophanates obtained by reacting an excess amount of these isocyanate compounds with low molecular weight active hydrogen compounds such as ethylene glycol, propylene glycol, meta-xylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, and meta-xylylenediamine, as well as high molecular weight active hydrogen compounds such as various polyester resins, polyether polyols, and polyamides.
[0067] The phosphoric acid-modified compound has the effect of improving the adhesive strength, and known and commonly used compounds can be used.Specific examples include phosphoric acid, pyrophosphoric acid, triphosphoric acid, methyl acid phosphate, ethyl acid phosphate, butyl acid phosphate, dibutyl phosphate, 2-ethylhexyl acid phosphate, bis(2-ethylhexyl)phosphate, isododecyl acid phosphate, butoxyethyl acid phosphate, oleyl acid phosphate, tetracosyl acid phosphate, 2-hydroxyethyl methacrylate acid phosphate, polyoxyethylene alkyl ether phosphoric acid, and the like, and one or more of these compounds can be used.
[0068] There are no particular limitations on the solvent, so long as it can dissolve the polyol and isocyanate compound, can uniformly disperse the phosphoric acid-modified compound and plate-like inorganic compound, and has a boiling point and volatility appropriate for the production process.
[0069] The plate-like inorganic compound has the effect of improving the laminate strength and gas barrier properties of the gas barrier adhesive layer obtained by curing the adhesive resin composition. Specific examples of the plate-like inorganic compound include kaolinite-serpentine group clay minerals (halloysite, kaolinite, endelite, dickite, nacrite, etc., antigorite, chrysotile, etc.), pyrophyllite-talc group (pyrophyllite, talc, kerolai, etc.), etc., and one or more of these can be used.
[0070] <Manufacturing method of film for bag-in-box container> The film for the inner container of the bag-in-box is produced by bonding a first layer and a second layer with an adhesive.
[0071] The adhesive is applied, for example, to the first layer by bar coating, dipping, roll coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, gravure offset, or the like. The coating film formed by applying the adhesive is dried, and then the second layer is laminated. The temperature during drying can be, for example, 30 to 200°C, and preferably 50 to 180°C. After the second layer is laminated, the coating film is cured. The temperature during curing can be, for example, room temperature to 70°C, and preferably 30 to 60°C. By setting the temperature during drying and curing within the above range, it is possible to suppress the occurrence of cracks in the adhesive layer.
[0072] <Bag-in-box container> Fig. 2 is an external view showing one embodiment of an inner container for a bag-in-box (hereinafter, sometimes referred to as "inner container"). As shown in Fig. 2, the inner container 20 is made by making a bag from a pair of inner container films 10. Specific examples of the bag making method include a method of blow molding a film, and a method of vacuum forming or pressure forming two films and fusing or sealing the periphery with heat or ultrasonic waves.
[0073] The pair of inner container films may be arranged so that the first layers face inward, or so that the second layers face inward. Alternatively, one inner container film may be arranged so that the first layer faces the inside, and the other inner container film may be arranged so that the second layer faces the inside. In order to achieve even better resistance to dropping bags, it is preferable that the pair of inner container films are arranged so that the first layers face the inside.
[0074] The inner container 20 is composed of a storage section for storing the contents, a spout 21, and a fused section 22 provided around the storage section. The contents are poured out through the spout 21. The spout 21 can include, for example, a pouring outlet fused to the inner container 20, and a cap that fits over the pouring outlet to enable it to be opened and closed.
[0075] The shape of the inner container can be a two-sided bag, a three-sided bag, a four-sided bag, a cube, or a rectangular parallelepiped, but two-sided bags, three-sided bags, and four-sided bags are preferred because they have better resistance to falling. When the inner container is dropped, an anisotropic impact is applied to the inner container, which may cause it to break at the location indicated by D. Since the inner container 20 is made of the film 10, breaking at the location indicated by D is suppressed.
[0076] From the viewpoint of more easily preventing leakage of contents due to external impacts or scratches during transportation and use of the bag-in-box, the inner container may include an inner bag made from the above-mentioned inner container film and an outer bag made from another film. That is, the inner container may be a double bag. The other film used for the outer bag may be the same film as that of the inner bag, or may be a different film. Examples of the different film include a polyethylene film and a polypropylene film. By using an olefin-based resin film as the film constituting the outer bag, the recyclability is improved. An inner container including an inner bag and an outer bag can be obtained by sealing the film constituting the outer bag around the inner bag.
[0077] <Bag in box> Fig. 3 is an external view showing one embodiment of a bag-in-box. As shown in Fig. 3, the bag-in-box 100 includes an inner container 20 having a spout 21 and an outer container 30 that houses the inner container 20. The inner container 20 is an inner container for a bag-in-box, produced from the inner container film for the bag-in-box. The spout 21 is provided so as to be continuous with the inner container 20 and to protrude to the outside of the outer container 30, and the contents are poured out through this spout 21.
[0078] The contents contained in the inner container include food and non-food liquids. Examples of the contents include food liquids such as fruit juice drinks, juice, carbonated drinks, tea, coffee, milk drinks, soups, and other beverages, and alcoholic beverages such as sake and shochu, and non-food liquids such as developing solutions, inks, paints, oils, disinfectants, liquid fertilizers, bactericides, and insecticides. Examples of the outer container 30 (outer box) include boxes made mainly of cardboard paper (corrugated cardboard boxes) and boxes made mainly of cardboard so as to withstand the weight of these contents.
[0079] <How to select film> The selection method according to the present embodiment is a method for selecting a film for a bag-in-box inner container. The selection method according to the present embodiment includes the following steps.
[0080] (a) preparing a film to be evaluated that has a first polyethylene-based resin layer, an adhesive layer, and a second polyethylene-based resin layer in this order and has a thickness of 200 μm or less; (b) preparing a first test piece comprising a first polyethylene-based resin layer and a second test piece comprising a second polyethylene-based resin layer; (c) A step of determining the mass (W1) of the dart at which the first test piece is broken, which is measured in accordance with JIS K 7124-1 Method A. (d) A process of determining the mass (W2) of the dart at which the second test piece is broken, which is measured in accordance with JIS K 7124-1 Method A. (e) determining that the film is acceptable when the mass ratio (W2 / W1) of the mass (W1) of the dart that breaks the first test piece to the mass (W2) of the dart that breaks the second test piece is 2.0 or more.
[0081] A method of performing a dart impact test on a film is considered as an evaluation of the resistance to a bag drop. However, this method is insufficient for evaluating the resistance to a bag drop. In the dart impact test, a hemispherical dart is dropped on a test piece, so that an isotropic impact is applied to the test piece. On the other hand, when the bag is dropped, an anisotropic impact is applied to the film due to the contents contained in the inner container. This impact generates a local distortion in the film, causing the bag to break. The method of performing a dart impact test on a film cannot adequately evaluate the resistance to a bag drop caused by such anisotropic impact. The present inventors have made it clear through their investigation that it is useful to measure W1 and W2 and use as a criterion whether or not the mass ratio of W1 and W2 is 2.0 or more for such a bag drop impact.
[0082] The size of the test piece prepared in step (b) may be 200 x 200 mm.
[0083] The measuring device used in the steps (c) and (d) is a dart impact tester. The shape of the dart may be hemispherical. When the dart is hemispherical, its diameter may be 38 mm. The height from the test specimen at which the dart is allowed to freely fall onto the test specimen may be 0.66 m.
[0084] The mass of the dart that breaks the test piece in steps (c) and (d) may be the mass at which the test piece is first broken when the mass of the dart is increased by 30 g each time. The mass of the dart used initially in steps (c) and (d) may be, for example, 50 g. The dart is composed of a jig and a weight. EXAMPLES
[0085] The present disclosure will be described in more detail with reference to the following examples, but the present disclosure is not limited to these examples.
[0086] <Examples 1 to 4 and Comparative Examples 1 to 4> The following materials were prepared: (Base film) Substrate 1A: LLDPE, MD tensile modulus of elasticity 180 MPa, TD tensile modulus of elasticity 230 MPa, MD stiffness strength 3 mN, TD stiffness strength 4 mN, unstretched film, thickness 40 μm, manufactured by Tamapoly Co., Ltd., product name "MZ180" Substrate 1B: LLDPE, MD tensile modulus of elasticity 180 MPa, TD tensile modulus of elasticity 230 MPa, MD stiffness strength 8 mN, TD stiffness strength 10 mN, unstretched film, thickness 60 μm, manufactured by Tamapoly Co., Ltd., product name "MZ180" Substrate 1C: LLDPE, MD tensile modulus 180 MPa, TD tensile modulus 230 MPa, MD stiffness 25 mN, TD stiffness 30 mN, unstretched film, thickness 90 μm, manufactured by Tamapoly Co., Ltd., product name "MZ180" Substrate 1D: LLDPE, MD tensile modulus 180MPa, TD tensile modulus 230MPa, MD stiffness 60mN, TD stiffness 75mN, unstretched film, thickness 120μm, manufactured by Tamapoly Co., Ltd., product name "MZ180" Substrate 1E: LLDPE, MD tensile modulus 180 MPa, TD tensile modulus 230 MPa, MD stiffness 120 mN, TD stiffness 140 mN, unstretched film, thickness 150 μm, manufactured by Tamapoly Co., Ltd., product name "MZ180" Substrate 2A: LLDPE, MD tensile modulus of elasticity 290MPa, TD tensile modulus of elasticity 390MPa, MD stiffness strength 5mN, TD stiffness strength 7mN, unstretched film, thickness 40μm, manufactured by Tamapoly Co., Ltd., product name "SE620" Substrate 2B: LLDPE, MD tensile modulus 290 MPa, TD tensile modulus 390 MPa, MD stiffness 100 mN, TD stiffness 130 mN, unstretched film, thickness 120 μm, manufactured by Tamapoly Co., Ltd., product name "SE620" Base material 3A: LLDPE, MD tensile modulus 400 MPa, TD tensile modulus 440 MPa, MD stiffness 20 mN, TD stiffness 20 mN, unstretched film, thickness 60 μm, manufactured by Idemitsu Unitech Co., Ltd., product name "MB203" Substrate 3B: LLDPE, MD tensile modulus 400 MPa, TD tensile modulus 440 MPa, MD stiffness 130 mN, TD stiffness 140 mN, unstretched film, thickness 120 μm, manufactured by Idemitsu Unitech Co., Ltd., product name "MB203" (glue) Maxive (gas barrier adhesive, manufactured by Mitsubishi Gas Chemical Company, Inc.) An epoxy adhesive was prepared by mixing 16 parts by mass of Maxive C 93T and 5 parts by mass of Maxive M-100 with 1 part by mass of a solvent made by mixing ethyl acetate and methanol in a mass ratio of 1:1.
[0087] The tensile modulus (MPa) of each substrate film was measured as follows. Each substrate film was cut into a rectangular shape with a total length of 200 mm and a width of 15 mm to prepare a test piece, which was attached to the fixed and movable grips of a tensile tester (a test device conforming to JIS K7127:1999) with a grip distance of 150 mm. The test temperature was set at 23°C, and the movable gripper was moved at a tensile speed of 50 mm / min, and the ratio of the tensile stress to the corresponding strain within the tensile proportional limit was determined. The average value for three test pieces was taken as the tensile modulus. The measurement results for the test pieces cut out such that the machine direction of the base film was the overall length direction of the strip were recorded as the MD tensile modulus, and the measurement results for the test pieces cut out such that the width direction of the base film was the overall length direction of the strip were recorded as the TD tensile modulus.
[0088] (Measurement of impact breakage mass in free-fall dart impact testing) For each substrate film, the mass of the dart at which the test piece was destroyed was determined according to JIS K 7124-1 A method. Specifically, the test piece (size: 200 × 200 mm) was set in a measuring device (dart impact tester). A hemispherical dart of φ38 mm was dropped onto the test piece from a height of 0.66 m from the test piece. First, a 50 g dart (weight of jig 50 g, no weight) was dropped onto the test piece. Then, the mass of the dart was changed by 30 g each to determine the mass of the dart at which the test piece was destroyed. For the laminated films of each of the examples and comparative examples described later, the ratio (W2 / W1) of the mass of the dart at which the second polyethylene resin layer was destroyed to the mass of the dart at which the first polyethylene resin layer was destroyed (W1) was calculated. The results are shown in Table 1.
[0089] (Production of film for bag-in-box container) An adhesive was applied to one of the substrate films using a wire bar and dried at 60°C to form an adhesive layer with a thickness of 3 μm, and then the other substrate film was laminated. Then, aging was performed at 50°C for 4 days. As a result, a laminate film having a structure of substrate film (first layer) / adhesive layer / substrate film (second layer) was obtained. The thickness of the obtained laminate film is shown in Table 1.
[0090] (Evaluation of bag making suitability) Two rectangular sheets measuring 500 mm x 400 mm were cut out from the laminated films of the Examples and Comparative Examples. The two laminated films were arranged so that the first layers faced each other. Then, the four edges of the laminated film were impulse sealed to prepare a packaging bag. The obtained packaging bag was observed and the bag-making suitability of the laminated film was evaluated according to the following criteria. The results are shown in Table 1. (standard) A: No wrinkles caused by heat damage B: Wrinkles caused by heat damage are visible (Evaluation of bag breakage resistance) (1) Preparation of packaging Two rectangular sheets measuring 500 mm x 400 mm were cut out from the laminates of the examples and comparative examples, and the four edges were impulse sealed to prepare a bag-in-box inner container. At this time, an opening for inserting the contents was formed in the inner container. The dimensions of the inner container were 500 mm x 400 mm. Next, each inner container was filled with 9500 mL of tap water, and the opening was sealed. An inner container filled with water was prepared.
[0091] (2) Drop bag test The obtained inner container was stored for one day in an environment of 23°C. After storage, the inner container was dropped 10 times from a height of 1 m. The inner container after the drop was checked for the presence or absence of breakage. For each of the examples and comparative examples, 10 inner containers were evaluated and the number of broken bags was counted. The results are shown in Table 1.
[0092] (comprehensive evaluation) The laminated films of the Examples and Comparative Examples were comprehensively evaluated according to the following criteria. A: The bag making suitability is "A" and the number of broken bags is one or less. B: Bag making suitability is "B" or the number of broken bags is 2 or more.
[0093] [Table 1] [Explanation of symbols]
[0094] 1...first polyethylene-based resin layer, 2...second polyethylene-based resin layer, 3...adhesive layer, 10...film for inner container, 10...film, 20...inner container, 21...spout, 30...outer container, 100...bag-in-box.
Claims
1. A film for a bag-in-box inner container, A first polyethylene resin layer; An adhesive layer; A second polyethylene resin layer; in this order, The following formula (1) is satisfied: The film has a thickness of 200 μm or less. 2.0≦W2 / W1...Formula (1) [In formula (1), W1 is the mass of a dart at which the first polyethylene-based resin layer is destroyed as measured in accordance with JIS K 7124-1 Method A, and W2 is the mass of a dart at which the second polyethylene-based resin layer is destroyed as measured in accordance with JIS K 7124-1 Method A.]
2. The film of claim 1 , wherein the adhesive layer has gas barrier properties.
3. The film of claim 1, wherein the adhesive layer has a thickness of 0.5 to 6.0 μm.
4. The film according to claim 1 , wherein the first polyethylene-based resin layer and the second polyethylene-based resin layer are unstretched films.
5. The film according to claim 1, wherein at least one of the first polyethylene resin layer and the second polyethylene resin layer has a stiffness strength in MD and TD of 30 to 300 mN.
6. An inner container for a bag-in-box, produced by making a bag from the film according to any one of claims 1 to 5.
7. A bag-in-box comprising an inner container having a spout and an outer container for accommodating said inner container, said inner container being the inner container for bag-in-box according to claim 6.
8. A method for selecting a film for a bag-in-box inner container, comprising the steps of: preparing a film to be evaluated, the film having a thickness of 200 μm or less and including a first polyethylene-based resin layer, an adhesive layer, and a second polyethylene-based resin layer in this order; preparing a first test piece made of the first polyethylene-based resin layer and a second test piece made of the second polyethylene-based resin layer; A step of determining a mass (W1) of the dart at which the first test piece is broken, which is measured in accordance with JIS K 7124-1 Method A; A step of determining the mass (W2) of the dart at which the second test piece is broken, which is measured in accordance with JIS K 7124-1 Method A; determining that the film is acceptable when the mass ratio (W2 / W1) of the mass (W1) of the dart that breaks the first test piece to the mass (W2) of the dart that breaks the second test piece is 2.0 or more; The film selection method includes:
Citation Information
Patent Citations
Gas barrier laminate and packaging bag
WO2021176948A1